Ammonia for civil aviation: a design and performance study for aircraft and turbofan engine - Sasi, Sarath; Mourouzidis, Christos; Rajendran, David John; Roumeliotis, Ioannis; Pachidis, Vassilios; Norman, Justin (Elsevier, 2024)
The 2050 net zero targets for aviation to decarbonize the industry means that solutions need to be delivered that can help achieve those targets. Transitioning to zero carbon aviation fuel is an effective solution to achieve those targets. This research article aims to highlight the potential design and performance implications of using Ammonia as a zero-carbon fuel for civil aviation through a retrofit case study conducted for an Airbus A350-1000 equivalent aircraft. The impacts on both turbofan design and aircraft payload-range capability are presented. A feasibility study of using Ammonia as a Hydrogen carrier for civil aviation is also presented. The turbofan design impacts, and payload range capability are assessed using Cranfield University’s in-house gas turbine performance tool TURBOMATCH and NASA FLOPS respectively. A 3-point turbofan cycle design strategy is utilized for redesigning turbofan engine cycles using Ammonia as a fuel. Ammonia fuel conditioning assessment is made using REFPROP to investigate its impact on turbofan design. Utilizing pure Ammonia as an aircraft fuel can provide significant turbofan redesign opportunities. Fuel conditioning assessment revealed that for a 430 kN thrust class engine, 2.1 MW of thermal power is required to condition Ammonia fuel at take-off. As a result, various strategies to condition the fuel and its significant impact on turbofan design are presented indicating fuel conditioning as a major design driver for Ammonia fuelled turbofan engines in the future. Although upon initial preliminary assessment, Ammonia utilized as a Hydrogen carrier showcased potential by providing additional mission range capability when compared to a pure Ammonia burning aircraft, the significant thermal energy required to crack (decompose) Ammonia into Hydrogen highlighted the challenges at aircraft mission level and Hydrogen turbofan design implications. It is found that energy requirement (power) to crack Ammonia into Hydrogen are significant which is approximately an order of magnitude higher than Ammonia fuel conditioning itself.
Keywords: Ammonia; Hydrogen; Alternative aviation fuels; Turbofan engines